Deposition processing and surface metrology of MoNx thin films by design of experiment and single variable (nitrogen flow rate) methods. (1st March 2023) - Chen, Fong-Zhi; Ting, I-Sheng; Kang, Wei-Zen; Lin, Yu-Wei; Huang, Jia-Hong
Abstract: In this study, the Taguchi design of experiment (DOE) was performed to optimize the deposition process of MoNx thin films using unbalanced magnetron sputtering (UBMS). Further single-variable experiments based on the sensitive parameter derived from the Taguchi experiments were conducted to investigate the effect of the parameter on the phase evolution, structure, and properties of the MoNx thin films. The MoNx thin films were deposited using DC-UBMS. Four controlling factors: N2 flow rate, substrate bias voltage, substrate temperature, and substrate rotational speed were selected in the Taguchi L9 matrix experiment. Electrical resistivity and hardness were chosen as the quality characteristics for the optimization. Analysis of variance (ANOVA) and analysis of mean (ANOM) were performed to identify the sensitive parameters and the optimum conditions. The confirmation test results for the optimizations of hardness (SH) and electrical resistivity (SR) were within the predicted ranges, and therefore the feasibility and reliability of the Taguchi optimization were verified. The results of ANOVA showed that nitrogen flow rate was the most sensitive factor. The optimum condition for the electrical resistivity was chosen to be the reference for the single-variable experiments, and nitrogen flow rate was selected as the controlling variable. The MoNx specimens in the single-variable experiment showed prevailing (200) texture that could be attributed to the lowest surface energy associated with (200) plane and the base metal steering effect by Mo (110). The results of single-variable experiments indicated that the retained Mo metal phase played an important role in hardness, electrical resistivity, and residual stress.